COMPARISON OF SILO TYPES ON CHEMICAL COMPOSITION AND PHYSICAL QUALITY OF SILAGE MADE FROM MAIZE, SORGHUM AND OATS FODDERS - Rafiuddin; M. Abdullah; K. Javed; M. A. Jabbar; M. Q. Shahid; P. S. Jan; M. Ramzan; M. A. Khan; M. Ahmad (Journal of Animal and Plant Sciences, 2017)
The objective of current study was to investigate the effects of trench, bunker and plastic bag silos on chemical and physical characteristics of silages made from three cereal fodders i.e. maize, sorghum and oats in subtropical conditions. Each fodder was harvested at 30-35% dry matter (DM) and ensiled in the said three silo types. The results revealed that trench silo had significantly (P<0.05) highest sensory score (smell, color and structure) followed by bunker and bag silo for each cereal silage. The sensory score for maize (12.99, 12.09 and 10.96), sorghum (11.17, 12.72, and 10.28) and oat silages (12.55, 13.27 and 11.47) corresponding to trench, bunker and bag silos, respectively. The lowest pH values were observed in trench followed by bunker and bag silos, in maize (3.61, 3.65 and 3.81), sorghum (3.71, 3.81 and 3.89) and oat silage (3.82, 3.87 and 3.93), respectively. However, the DM and crude protein (CP) were significantly (P<0.05) higher in trench followed by bunker and bag silos. In-vitro dry matter digestibility (IVDMD) also varied significantly (P<0.05) among silo types. The higher IVDMD% for maize (65.83, 64.53 and 63.00), sorghum (62.23, 60.43 and 58.00) and oats (59.60, 58.6 and 57.16) silages were observed in trench followed by bunker and bag silo, respectively. The current findings revealed that silage quality was highest in trench silo for cereal fodders in subtropical conditions.
Keywords: Silo types; cereal silages; physical and chemical quality